Investigating Postpartum Depression in Mothers of Children With Cleft Lip and Palate - Parastoo Namdar; Hossein Abdali; Atena Shiva; Mehdi Pourasghar; Sahar Talebi (Mazandaran University of Medical Sciences, 2024)
Background and Objectives: Postpartum depression (PPD) is a subtype of major depressive disorder, which is correlated with having an infant with cleft lip and palate (CL/P). Since there is a dearth of research in this regard, this study compares mothers of infants with CL/P and mothers of normal infants in terms of PPD and suicidal thoughts.  Methods: This descriptive-analytical study was conducted on 50 mothers of children with CL/P and 50 mothers of normal children who had recently given birth and presented to the Research Center of Cranial Deformities, Isfahan University of Medical Sciences, Isfahan City, Iran, from September 2020 and 2021. The Edinburgh postnatal depression scale was used to assess PPD.  Results: The mean PPD score was 15.42±4.77 (range=5-24) and 10.3±6.7 (range=0-29) in mothers of children with CLP and those with normal children, respectively. The frequency of PPD was significantly higher among the mothers of CLP children, compared to mothers of normal children (χ2=25.25, P<0.005). No difference was reported between the mothers with PPD and those without it in terms of educational level (χ2=0.36, P=0.83), occupational status (χ2=0.13, P=0.71), or parity (P=0.93). Having suicidal thoughts had no significant correlation with having CL/P children (P=0.11).  Conclusions: The PPD score and frequency of PPD were higher among mothers of children with CLP, compared with mothers of normal children; however, the frequency of suicidal thoughts was not significantly different between the two groups. Educational level, occupational status, and parity were not correlated with PPD or suicidal thoughts.